2016
DOI: 10.1108/tr-02-2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

Brand personality, brand equity and revisit intention: an empirical study of a tourist destination in Iran

Abstract: Purpose The purpose of this paper is to examine how brand personality and brand equity affect intentions to revisit a city tourism destination. Design/methodology/approach Statistical population of this research consisted of those visitors who traveled to Pool city in Iran during Spring 2015. A structural equation model test with maximum likelihood estimation was performed to test the relationship among the research variables using 367 participants. Findings The empirical results from the structural model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 77 publications
2
32
0
6
Order By: Relevance
“…Impact of psychological entitlement (Salehzadeh et al, 2016). Table 5 shows the regression coefficients and values of CR and p associated to each hypothesis.…”
Section: Perceived Organizational Justice Psychological Entitlement Cyberloafingmentioning
confidence: 99%
“…Impact of psychological entitlement (Salehzadeh et al, 2016). Table 5 shows the regression coefficients and values of CR and p associated to each hypothesis.…”
Section: Perceived Organizational Justice Psychological Entitlement Cyberloafingmentioning
confidence: 99%
“…In addition, brand equity is an appropriate metric for evaluating the long-term impact of marketing decisions (Atilgan et al, 2005;Zavattaro et al, 2015;Liu and Chou, 2016). Proper management of brand equity leads to further customer loyalty and revisit intentions (Salehzadeh et al, 2016), less risk in marketing activities and crises, flexible responses to price volatility, more inter-organisational cooperation, improved effectiveness of marketing communications, better opportunities for brand reputation, higher attractiveness for investors (Aaker, 1991;Keller, 2003;Samu et al, 2012;Han et al, 2015), increased profit margins (Kotler and Keller, 2011), more opportunities for attracting good employees (Del Vecchio et al, 2007) and higher protection against the arrival of potential competitors during outsourcing (Lim and Tan, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In accord with this view, several studies found a positive association between brand personality and brand equity, notably in diverse domains such as sales promotions (ValetteFlorence, Guizani, and Merunka 2011), tourist revisit intentions (Salehzadeh, Khazaei Pool, and Soleimani 2016), and service industry brands (Loureiro et al 2014). These studies, however, rely mostly on the mainstream brand equity dimensions such as brand awareness, brand loyalty, and brand associations.…”
Section: Hypotheses Development Media Type and Brand Personalitymentioning
confidence: 94%